Crossover pedagogy : a rationale for a new teaching partnership between faculty and student affairs leaders on college campuses - Nash, Robert J.; Jang, Jennifer J. J.; Nguyen, Patricia C. (Emerald Publishing Limited : IAP, Information Age Publishing, Inc., 2016)
As authors, we are convinced that the time has finally arrived in academe for an extensive, experience-based, firsthand, seamless examination of what we are calling crossover pedagogy. There is no book-length examination of facultystudent affairs administrators collaboration in the academic realm anywhere. Nobody has yet to produce a case-based, hands-on, book-length treatment of how (and why) faculty and student affairs administrators can co-teach, co-author, and co-consult with one another as co-equal educators and campus leaders--with each group complementing the other in terms of their special skills, knowledge, background, and experiences. Without coming to practical terms with the case for collaboration that the above authors make, the why rationale developed in these publications on the topic of faculty-administrator collaboration (sometimes referred to as 'blended' efforts) around the teaching-learning venture is lost in the logistics of technical policy issues and challenges.